On Measuring the Variance-Age Profile of Lifetime Earnings - Eden, Benjamin; Pakes, Ariel (Review of Economic Studies, 1981)
Benjamin Eden, Ariél Pakes; On Measuring the Variance-Age Profile of Lifetime Earnings, The Review of Economic Studies, Volume 48, Issue 3, 1 July 1981, Pa